An Empirical Study of Factors Influencing Fintech Adoption in Nepal - Tamang, Sushan (Apex Journal of Business and Management, 2026)
Nepal’s financial sector lags in FinTech adoption despite global advancements, limiting financial inclusion. This study examines behavioral, usability, and trust factors driving FinTech uptake among urban and rural populations. Data from 313 respondents were gathered via structured questionnaires and analyzed using descriptive statistics, reliability tests, correlation, regression, and mediation analysis to test TAM/UTAUT frameworks alongside perceived risk and trust dimensions. Perceived usefulness, ease of use, effort/performance expectancy, social influence, and service/agent trust significantly predict adoption intentions. Behavioral intention, perceived risk, and usability mediate these relationships, with risk exerting negative effects. Younger, digitally literate students and employed individuals emerge as primary adopters. Findings urge policymakers and FinTech providers to prioritize digital literacy campaigns, trust-building initiatives, intuitive interface design, and risk mitigation strategies. Targeted interventions for rural and older demographics can accelerate inclusive digital finance, bridging Nepal’s urban-rural divide.